Virreinal hydraulic model used in the Historic Center of Lima for water supply - Gonzalez Espino, David (2020)
The objective of the work is the design of the Virreinal hydraulic model in the Historic Center of Lima, starting from a pre-Hispanic system that developed under the waters of the Rímac river. From the foundation of the city new architectural technologies are used as well as the use of materials to develop a model capable of correctly managing water in the city. With urban growth there are aqueducts, secondary canals, water boxes, nozzles, pipes, fountains and sewers that will be part of the hydraulic model of the city of Lima that will serve to supply water to its neighbors in this viceregal stage.